People and Machines: A Look at the Evolving Relationship Between Capital and Skill in Manufacturing 1860-1930 Using Immigration Shocks - Jeanne Lafortune; José Tessada; Ethan Gatewood Lewis (Institute for the Study of Labor (IZA), 2015)
This paper estimates the elasticity of substitution between capital and skill using variation across U.S. counties in immigration-induced skill-mix changes between 1860 and 1930. We find that capital began as a q-complement for skilled and unskilled workers, and then dramatically increased its relative complementary with skilled workers around 1890. Simulations of a parametric production function calibrated to our estimates imply the level of capital-skill complementarity after 1890 likely allowed the U.S. economy to absorb the large wave of less-skilled immigration with a modest decline in less-skilled relative wages. This would not have been possible under the older production technology.
Keywords: J24; N61; O33; 330; immigration; capital-skill complementarity; skill-biased technical change; manufacturing; Second Industrial Revolution